Influence of controlled breath on healthy adult autonomic heart modulation - Léo José Rubin Neto; Katieli Santos de Lima; Murilo Rezende de Oliveira; Natiele Camponogara Righi; Rodrigo Boemo Jaenisch; Gustavo Orione Puntel; Antonio Marcos Vargas da Silva; Luis Ulisses Signori (Universidade Estadual de Maringá, 2023)
Heart rate variability (HRV) is a technique that indirectly assesses the activities of the autonomic nervous system in the heart. However, during data collection there are controversies regarding the use of spontaneous or controlled breath. The aim of this research was to compare the effects of controlled and spontaneous breath on HRV in healthy adults.The present cross-sectional study held a sample of 52 healthy volunteers (22 male, 42.3%), average of 25 (±4) years old and body mass index 22.4 (±2.7) kgm-². All the volunteers were evaluated in 2 days (at most three days between the evaluations). On each day the data were collected with spontaneous and then controlled breath (12 breaths per minute - bpm: Inspiration/Expiration: 2/3). Data were collected with a pulse frequency meter (Polar brand, model 810i). The HRV was evaluated for time and frequency domain and was analyzed using an area corresponding to 5 minutes (containing at least 256 beats per minute) by Kubios program version 2.1. In the time domain, no differences were observed between spontaneous and controlled breath. In the frequency domain, the controlled breathing reduced sympathetic activity (p<0.001) in approximately 14% and increased (p<0.001) parasympathetic activity proportionally. The autonomic modulation evaluated by low frequency/ high frequency(LF/HF) ratio decreased (p<0.001) in average -0.6 on the days evaluated. The controlled breathing (12 bpm) decrease sympathetic activity and increases parasympathetic by modifying the heart autonomic modulation.